A highly cost-effective, eco-friendly tissue lysis and extraction method for faster DNA isolation from fish fin - Pritam Lenka; Namrata Singh; Deepra Ghosh; Vivekanand Mahato; Sajalendu Ghosh (PLoS ONE, 2025)
Proper DNA extraction is an essential step in molecular biology research, for various downstream applications. Several modifications have been made to the first extraction protocol by Friedrich Miescher in 1869. The current work aimed to standardize an eco-friendly and quicker DNA extraction process that could be used in resource-limited laboratories by utilizing low-priced household liquid detergents and easily accessible salt. The pectoral fin tissues were lysed at 58°C with two modified lysis buffers using detergent 1 & 2 along with the conventional lysis buffer (SDS) as control. Instead of extraction with organic solvents, a 5M edible salt solution was used. This modified protocol resulted in yielding 3269.67 (±108.7) ng/µl and 3000 (± 15) ng/µl of DNA using detergent 1 and 2 with comparable quality of DNA as confirmed by OD260/280, i.e., 1.7 (± 0.026) and 1.72 (± 0.015) respectively, while the conventional method gave a maximum of 2512.33 (± 45.78) ng/µl of DNA with 1.76 (± 0.021) OD260/280 values. The overall cost of the proposed protocol was found almost 32 times less than the conventional method. The quality of DNA obtained by the modified protocol was pure enough to be used in PCR amplification of both nuclear (microsatellite) and mitochondrial (COX1) DNA for further application of genotyping. This modified protocol for DNA extraction from fish fin was faster (half the time required than the SDS lysis), of comparable quality and even better quantity with significantly lesser overall cost, and can be recommended for DNA extraction from fish samples in any resource-constrained laboratories.